'Are you prepared?' Representations and management of floods in Lomanikoro, Rewa (Fiji). Issue 4 (8th January 2016) - Nolet, Emilie
Abstract : The islands of Fiji, in the Western Pacific, are exposed to a wide range of natural hazards. Tropical storms and associated floods are recurring natural phenomena, but it has been regularly alleged that Fijians lack preparation, over‐rely on state assistance in post‐disaster situations or engage in risky behaviours that aggravate the negative impact of floods. Risk reduction strategies, which are now implemented by government authorities and international organisations, heavily promote the principle of 'community preparedness'. Both community awareness programmes and capacity‐building programmes are conducted throughout the country in the most vulnerable communities. This paper analyses how the inhabitants of Lomanikoro village, in the low areas of the Rewa Delta, perceive and manage existing flood risks. It examines social and cultural factors that contribute to shape risk response locally—in particular, why villagers may be reluctant to adopt some recommended preparedness measures and resettle in higher, safer zones.